Sulfonated Polystyrene/Polybenzimidazole Bilayer Membranes for Vanadium Redox Flow Batteries - Ikhsan, Muhammad Mara; Abbas, Saleem; Do, Xuan Huy; Ha, Heung Yong; Azizi, Kobra; Henkensmeier, Dirk (Wiley-VCH Verlag, 2025)
Polybenzimidazole has been widely examined as a separator for vanadium redox flow batteries (VRFBs) due to its low vanadium permeability. Its low conductivity can be tackled by combining 1–4 µm thin dense PBI layers with highly conductive mechanically supporting layers, either by lamination or loose stacking. While gel-PBI is very soft and conductive, the shadow effect of the non-conductive pore walls of porous supports adds resistance. In this work, these issues are addressed by coating a 25 µm thick highly conductive sulfonated polystyrene layer (S) with a 1 µm thin selective PBI layer (P) to block vanadium crossover. To reduce the number of potential defects, two bilayer membranes can be stacked. A 52 µm thick stack of two membranes (PS–SP, PBI faces the electrodes) shows an area-specific resistance of 144.8 mΩ cm2 in VO2+-containing electrolyte and a permeability of 6.85 × 10−14 m2 s−1, both lower than the values for Nafion 212. A VRFB cell test over 3500 charging cycles (1660 h) with an energy efficiency of up to 88.5% at 100 mA cm−2 is shown. Performance losses are reversed by electrolyte rebalancing. With material costs of 1.84 USD m−2, the PSSP(1-25-25-1) membrane promises high performance at low costs.